Compliance costs of Malaysia's small and medium enterprises - Mohd Hanefah, Mustafa; Kasipillai, Jeyapalan (2000)
This study presents compliance costs of Malaysia's Small and Medium Enterprises (SMEs) for the income tax assessment year 1998.These estimates obtained from a representative population using personal interviews suggest that the level of compliance costs, which are made of computational and planning costs is substantially greater for SMEs compared to public listed companies.For instance, the average tax paid by the SMEs is merely one-eleventh of the taxes paid by a typical listed firm.The average tax paid by the SMEs is merely one-eleventh of the taxes paid by a typical SME. This indicates that the compliance cost is three and a half times more regressive for an average SME. The study is particularly significant for Malaysian taxpayers (including SMEs) as the self-assessment system will be implemented in stages, commencing with companies, in 2001.